Management of a patient with hypercortisolism (Cushing’s disease/syndrome, hypercorticism with predominant secretion of mineralocorticoids, estrogens, androgens)» [Electronic resource] - Tykhonova, Tetiana M.; Gorshunska, Maryana Yu.; Barabash, Nadiya Ye.; Martymianova, Larysa O.; Тихонова, Тетяна Михайлівна; Горшунська, Мар’яна Юріївна; Барабаш, Надія Євгенівна; Мартим’янова, Лариса Олексіївна (Kharkiv : V.N.Karazin National University, 2024)
The methodological recommendations outline the main aspects of the management of patients with hypercorticism syndrome, which include diagnosis and differential diagnosis of its individual forms, modern approaches to treatment. For students of the 6th year to prepare for practical classes in the discipline «Internal Medicine».
Ведення пацієнта з синдромом гіперкортицизму (хворобою/синдромом Іценка-Кушинга, гіперкортицизмом з переважною секрецією мінералокортикоїдів, естрогенів, андрогенів) [Електроний ресурс]
Keywords: гіперкортицизм; MEDICINE; синдром Іценка-Кушинга; хвороба Іценка-Кушинга; гіперкортизолізм; гіперальдостеронізм; фемінізація; вірилізація; адреногенітальний синдром; hypercorticism; Cushing’ssyndrome; Cushing’sdisease; hypercortisolism; hyperaldosteronism; feminization; virilization; adrenogenitalsyndrome